2010
DOI: 10.1021/ja910055a
|View full text |Cite
|
Sign up to set email alerts
|

Solar Driven Water Oxidation by a Bioinspired Manganese Molecular Catalyst

Abstract: A photoelectrochemical cell was designed that catalyzes the photooxidation of water using visible light as the sole energy source and a molecular catalyst, [Mn(4)O(4)L(6)](+) (1(+), L = bis(methoxyphenyl)phosphinate), synthesized from earth-abundant elements. The essential features include a photochemical charge separation system, [Ru(II)(bipy)(2)(bipy(COO)(2))], adhered to titania-coated FTO conductive glass, and 1(+) embedded within a proton-conducting membrane (Nafion). The complete photoanode represents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
357
0
6

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(372 citation statements)
references
References 29 publications
3
357
0
6
Order By: Relevance
“…Less attention has been paid to the development of earth-abundant sensitizers-an important problem for WS-DSPECs where absorber-to-catalyst ratios can exceed 1,000:1. Ruthenium polypyridyl sensitizers are most commonly used in WS-DSPECs (10,(16)(17)(18)(19), although Moore et al (20) demonstrated a WS-DSPEC sensitized with a zinc porphyrin that produced modest photocurrent (∼30 μA/cm 2 ). Organic sensitizers (containing C, H, N, and O) are earth abundant and offer the possibility of being low cost.…”
mentioning
confidence: 99%
“…Less attention has been paid to the development of earth-abundant sensitizers-an important problem for WS-DSPECs where absorber-to-catalyst ratios can exceed 1,000:1. Ruthenium polypyridyl sensitizers are most commonly used in WS-DSPECs (10,(16)(17)(18)(19), although Moore et al (20) demonstrated a WS-DSPEC sensitized with a zinc porphyrin that produced modest photocurrent (∼30 μA/cm 2 ). Organic sensitizers (containing C, H, N, and O) are earth abundant and offer the possibility of being low cost.…”
mentioning
confidence: 99%
“…Previous reports have appeared describing photocurrents and water oxidation by various combinations of chromophores and catalysts on TiO 2 (26)(27)(28)(29)(30)(31), most notably by Mallouk and coworkers (32), but typically with small photocurrents, low efficiencies, and limited stabilities. The core-shell molecular assembly approach described here offers a general platform for using chromophorecatalyst assemblies and it should open the door to a host of DSPEC applications.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the water oxidation complex involves a cubic cluster with four Mn atoms bridged via oxygen atoms (8,9). To study the principles governing photosynthesis, molecular systems with structures comparable to the Mn 4 O 5 Ca cluster having a [Mn 4 O 4 ] core have been studied (10,11). Mn is not only an abundant element, but also occurs in easily switchable oxidation states.…”
Section: Artificial Photosynthesis | Water Oxidationmentioning
confidence: 99%